301POncological outcome following 3 Drug NACT for Bucco-Alveolar carcinoma with Supra-notch ITF extension. (24th November 2019) - Gupta, K; Mandlik, D; Patel, K
Abstract: Background: Bucco-alveolar carcinoma is a clinical entity prevalent in Asia. These cancers have early involvement of Infra-temporal fossa (ITF) and subsequent poor oncological outcomes. Locally advanced Bucco-alveolar complex carcinoma (T4b) with supra-notch (supra-sigmoid) ITF extension is oncological challenge with poor outcome. We analysed oncological outcome in patients managed with 3-drug Neo-adjuvant chemotherapy (NACT) followed with surgical compartmental resection and adjuvant chemoradiation. Methods: 33 cases of T4b Bucco-alveolar complex carcinoma with supra-notch ITF extension included from June 2009 to January 2017. Patients received 3-Drug NACT (3-day regimen: IV Cisplatin 75 mg/m2 or IV Carboplatin 70 mg/m2 + IV Docetaxel 75 mg/m2 + IV 5-FU 1000 mg/m2) for 2-3 cycles every 21 days. Response assessed with clinical examination, improvement in symptoms (improved mouth opening etc.) and Response Evaluation Criteria In Solid Tumors (RECIST) criterion. Patients showing good response on NACT underwent Compartmental surgical resection with complete ITF clearance followed by adjuvant chemoradiotherapy (5-6 cycles weekly Inj. Cisplatin with 60Gy/30# RT). Data analyzed using STATA 13 and Kaplan Meir graphs for survival rates. Results: 31 patients (93.9%) showed response on NACT and underwent Surgery, with 2 patients showing disease progression after 1st cycle of NACT were treated non-surgically with palliative intent. Clinical response according to RECIST criterion & subjective clinical improvement > 50% was noted in 18 cases while < 50% in 13 cases. 22 of 31 patients were disease free with 7 loco-regional recurrences. There were no recurrences in ITF. Overall survival and disease-free survival rate was 81.8% and 70.9% respectively at mean follow-up of 30 months. Conclusions: 3-drug NACT followed by surgical resection in cases showing response to NACT with adjuvant chemoradiation provides a realm of hope for these borderline resectable T4b supra-notch cases. NACT provides an opportunity to attain better microscopically negative resection margins and helps in proper bio-selection of cancers according to their radio-chemosensitivity and response leading to better oncological outcomes. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.